Endohyphal bacteria from fungal endophytes of the Mediterranean cypress (Cupressus sempervirens) exhibit in vitro bioactivity. Issue 6 (10th April 2016) - Pakvaz, S.; Soltani, J.
Summary: Endohyphal organisms of endophytic fungi can induce, or promote, beneficial effects of their respective host fungi to the host plant that harbours them. The Cupressaceae plant family (Coniferales) hosts highly bioactive endophytic fungi. Here, we show that a fraction of such endophytic fungi harbours bioactive endohyphal bacteria with a non‐obligatory symbiotic lifestyle. Indeed, 5 of 16 (31.25%) endophytic fungi of Cupressus sempervirens harboured endofungal bacterial strains of Bacillaceae (G +, Bacilli) and Sphingomonadaceae (G −, α‐Proteobacteria), that is Bacillus pumilus (from the fungi Leptosphaeria CSE211 and Pyrenochaeta CSE134 ), Bacillus subtilis (from the fungi Leptosphaeria CSE212 and Ascorhizoctonia CSE148 ) and Sphingomonas paucimobilis (from the fungus Ascorhizoctonia CSE195 ). Notably, each endophytic fungal species contained only one endofungal bacterial species that was stably maintained in symbiosis over several rounds of subculturing. Moreover, we investigated whether cypress endofungal bacteria (CEB) could benefit their host fungus competing with other fungi and bacteria or the host plant against the invading microorganisms. In vitro assays indicated that CEB possessed antagonistic activity against cypress endophytic and pathogenic microbiome. Also, CEB metabolites and volatile compounds (VOCs) exhibited antifungal and antibacterial activity against the target microbiome. Bioactivity of CEB was less than that of the endophytic microbiome of Cupressaceae, on which we reported earlier. In conclusion, our work is the first to document endohyphal bacteria of fungal endophytes of C. sempervirens and the bioactivity of such endohyphal symbionts. These findings implicate a complicated interrelationship among host plant, endophytic microbiome and endofungal bacteria, which might be of high importance for evolutionary, as well as environmental and agricultural studies. Eventually, endohyphal bacteria may be introduced as a novel source for lead molecule discovery.